Genotoxic exposure during juvenile growth of mammary gland depletes stem cell activity and inhibits Wnt signaling. - Kristine S Klos; Soyoung Kim; Caroline M Alexander (PLoS ONE, 2012)
Various types of somatic stem cell have been tested for their response to genotoxic exposure, since these cells are likely to be important to regeneration, aging and cancer. In this study, we evaluated the response of mammary stem cells to genotoxic exposure during ductal growth in juveniles. Exposure to the polycyclic aromatic hydrocarbon (DMBA; 7,12 dimethylbenz[a]anthracene) had no gross effect on outgrowth and morphogenesis of the ductal tree, or upon lobuloalveolar growth during pregnancy. However, by fat pad assay, we found that mammary stem cell activity was reduced by 80% in glands from adults that were exposed to genotoxins as juveniles. The associated basal cell lineage was depleted. Both basal and luminal cells showed a robust response to genotoxic exposure (including γH2AX phosphorylation, pS(15)p53 and pT(68)Chk2), with durable hyperproliferation, but little cytotoxicity. Since the phenotype of these glands (low basal cell fraction, low stem cell activity) phenocopies mammary glands with loss of function for Wnt signaling, we measured Wnt signaling in genotoxin-exposed glands, and found a durable reduction in the activation of the canonical signaling Wnt receptors, Lrp5/6. Furthermore, when mammary epithelial cells were treated with Wnt3a, DMBA exposure reduced the basal cell population and Lrp activation was ablated. We conclude that during active ductal growth, Wnt-dependent mammary stem cells are sensitized to cell death by genotoxin exposure. Our conclusion may be important for other tissues, since all solid tumor stem cell activities have been shown to be Wnt-dependent to date.